New therapeutic options for metabolic‐associated steatotic liver disease - Tessa Straatmijer; Midas Mulder (British Journal of Clinical Pharmacology, 2026)
An increasing number of patients are being diagnosed with metabolic dysfunction‐associated steatotic liver disease (MASLD). MASLD results from disturbances in hepatic lipid metabolism and is associated with an increased risk of cirrhosis and hepatocellular carcinoma and significant extrahepatic morbidity, including cardiovascular disease and malignancies. The pathogenesis of MASLD stems from a multifactorial interaction among genetic susceptibility, epigenetic modifications and environmental factors, which collectively impair systemic metabolic homeostasis. Current management relies on a combination of lifestyle modification and pharmacotherapy. Resmetirom is the first drug registrated for the treatment of adults with MASLD and moderate to advances fibrosis. Over the next decade, multiple promising pharmacotherapies with diverse mechanisms of action and routes of administration are expected to become available for the treatment of MASLD. This narrative review provides an overview of the evolving pharmacological therapeutic landscape for MASLD, with a focus on novel therapeutic agents in late‐stage clinical development as THR‐β Agonists, GLP‐1 Receptor Agonists, Dual GLP‐1/ GIP Agonists, Glucagon/GLP‐1 Dual Agonists, FGF‐21 Analogues, Pan‐PPAR Agonists and FASN Inhibitors. Based on the differences in mechanisms of actions and specific side effects of these therapies, the characteristics of patients with MASLD should be taken into account in the decision which pharmacologic treatment should be initiated in an individual patient. Also, combining different therapies could be beneficial since this appears to possess complementary mechanisms.